State-level immigrant policies and diabetes prevalence in Latino and Asian American groups: a weighted multilevel analysis - Elizabeth Vásquez; Jennifer Toller Erausquin; Sandra E Echeverria; Md Towfiqul Alam; Erica Payton (BMJ Public Health)
Introduction Growing literature has shown that immigrant-related policies influence population health by limiting or enhancing immigrants’ rights. However, less is known about the role of state-level immigrant policies shaping chronic health conditions such as type 2 diabetes (T2DM). This cross-sectional study examined the association between state-level immigrant policies (both criminalising and inclusive) and prevalence of T2DM among individuals of Latin American and Asian American origin.Method We included adults aged 18+years sampled in the 2014–2018 behavioral risk factor surveillance system (BRFSS) (n=201 824), a survey design that allows the calculation of state-level estimates. Using existing policy measures, states were classified as low, moderate, or high on two dimensions: (1) criminalising and (2) inclusive policies. Weighted multilevel logistic regression models examined associations between state-level policy measures and self-reported T2DM after accounting for the complex survey design of BRFSS.Results Compared with Asians, Latinos were more likely to live in high criminalising policy states (35.2% vs 14.1%, p value <0.0001) and less likely to live in high inclusive policy states (63.1% vs 68.9%, p value <0.0001). Latinos also had higher T2DM prevalence than Asians (11.2% vs 8.7%, p value<0.0001). Adjusted models indicated that Latinos living in low inclusive policy contexts had significantly higher odds of T2DM (adjusted OR: 1.21, 95% CI 1.03 to 1.43) than Latinos living in high inclusive contexts. There were no statistically significant associations between criminalising policies and T2DM in either group.Conclusion Latinos had a higher burden of diabetes when living in states with low inclusive immigrant policies. Public health efforts should advocate for policies that create contexts that support the health of immigrants and their myriad contributions to the socioeconomic, and cultural fabric of the USA.